PERBANDINGAN ESTIMASI ANGGARAN BIAYA DENGAN METODE SNI DAN BOW - Mahardika Rahmawan Putra; Nur Azizah Affandy (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2017)
The  concept  of  drafting  the  Budget  Plan  (RAB)  project  is  done  based  on  an  analysis  of each constituent component  for every  work items on the entire project. This calculation analysis use two methods, SNI method and BOW method. This calculation uses the analysis of unit price in 2016.  From  the  calculation,  the  analysis  of  unit  prices  in  the  construction  of  religious  ministry office  in  Lamongan  Regencyshows  that  the  budget  estimation  using  SNI  method  is  more economical.  SNI  method  has  more  economical  budget  in  the  amount  of  Rp.  709,743,313.65 compared to BOW method, amountedRp 1,759,104,217.65. The difference of those two methods is Rp.  1,049,360,904.  This  result  occurs  because  the  coefficient  for  SNI  method  is  lower  than  the BOW method.